Implementasi Growth Mindset Untuk Meningkatkan Kinerja OSIS Di SMPN 7 Tangerang Selatan - Karsono, Edi; Fauji, Ahmad; Yulianti, Anti; Kusuma, Dara Astri; Citra, Nok; Pratiwi, Noni; Saendi (CV. Kurnia Grup, 2026)
The Student Council (OSIS) plays a strategic role in developing leadership and social skills among students; however, its organizational performance often faces challenges, particularly related to mindset, self-confidence, and the ability to deal with organizational challenges. This condition highlights the need for interventions that address not only technical skills but also psychological aspects. This community service activity aims to improve the performance of OSIS administrators through the implementation of a growth mindset integrated with strengthening organizational culture. The method used is a participatory-educative approach consisting of preparation, implementation, evaluation, and follow-up stages. The program was conducted through socialization, interactive training, group discussions, and experiential simulations, involving 30 OSIS administrators as participants. Evaluation was carried out using pre-test and post-test instruments as well as behavioral observations during the activity. The results indicate an increase in participants’ understanding of growth mindset concepts, accompanied by more positive attitudes toward challenges and failure. In addition, improvements were observed in active participation, self-confidence, teamwork, and communication skills. These findings demonstrate that an integrative approach combining growth mindset and organizational culture is effective in enhancing student organizational performance. Therefore, this activity contributes practically to the development of community service models based on educational psychology that are relevant to student character development in school environments.